784 The landscape of paediatric procedural sedation in UK & Irish emergency departments; a PERUKI study. Issue 3 (21st February 2022) - Hall, Dani; Moriarty, Tadgh; O'Sullivan, Ronan; Blackburn, Carol; Roland, Damian; Hartshorn, Stuart; Messahel, Shrouk; Lyttle, Mark D
Abstract : Aims/Objectives/Background: Approximately 250, 000 children undergo paediatric procedural sedation (PPS) in UK and Irish emergency departments (ED) annually. In comparison to other countries, PPS practice in our setting has not been described. We therefore aimed to evaluate PPS practice in UK and Irish EDs. Methods/Design: Online survey distributed through Paediatric Emergency Research in the UK and Ireland (PERUKI) during June 2020. One respondent per ED completed the survey, including questions on indications, agents, staffing and governance. Results are presented using descriptive statistics. Results/Conclusions: 61/72 (85%) sites responded, of which PPS was performed in 50 (82.0%). Intravenous ketamine was the most common agent (43/50; 86%), followed by fixed concentration nitrous oxide (FCNO, 35/50; 70%), and variable concentration nitrous oxide (VCNO, 13/50; 26%). PPS was mostly performed a few times a week (17/50; 34%) or daily (9/50; 18%). The most frequent indications were wound closure (31/50; 62%), orthopaedic reduction (28/61; 56%) and foreign body removal (17/61; 34%). Required sedationist seniority was highest for propofol and ketamine/es-ketamine (requiring consultant, registrar, or ANP), whilst FCNO was widely delivered by nurses and SHOs. Most sites had a guideline (43/61; 70.5%), documentation proforma (39/61; 63.9%) and equipment (36/61; 59.0%) and patient checklists (41/50; 82%). Explicit discharge criteria were required for ketamine/es-ketamine (40/45; 88.9%), midazolam (9/10; 90%), propofol (7/10; 70%) and VCNO (9/13; 69.2%). Databases existed in 24/61 (39.3%). We have demonstrated wide PPS use, but non-standardised practice, with only two-thirds of sites using a PPS guideline and standardised proforma. This leads to potential issues of risk and variability, highlighting a need for a UK and Ireland sedation package to standardise PPS practice and data collection, informed by international guidance and evidence. We propose development of a prospective ED sedation registry to facilitate data collection to support research within this area.